On the oscillons in the signum-Gordon model. Issue 1 (2nd January 2017) - Świerczyński, Z.
Abstract : New periodic solutions of signum-Gordon equation are presented. We first find solutions φ 0 ( x, t ) defined for ( x, t ) ∈ ℝ × [0, T ] and satisfying the condition φ 0 ( x, 0) = φ 0 ( x, T ) = 0. Then these solutions are extended to the whole spacetime by using (2.4).